A closer look at the main actors of Neotropical floodplain food webs: functional classification and niche overlap of dominant benthic invertebrates in a floodplain lake of Paraná River - Saigo, Miguel (2016)
Functional classifi cation of animals is necessary to enhance the predictive power of food web models. However, while there is a large database for functional classifi cation of benthic invertebrates (Functional Feeding Groups, FFG) in the temperate zone, the attribution of individual species of riverine invertebrates is still in its infancies in the Neotropical Region. Diff erent authors hypothesized that diet breadth was larger in the Tropics, however detailed analyses are scarce. In the present study we aimed at classifying dominant benthic taxa of the Middle Paraná River floodplain (Argentina) into trophic guilds by diet and niche overlap analysis. We sampled twelve taxa of benthic invertebrates from a fl oodplain lake during low water season and performed a gut content analysis as a baseline for FFG classifi cation. We also used available diet information of other common taxa for statistical analysis. Then, we compared the variance of niche overlap, using Pianka?s index, with that of simulated null model. After that we grouped taxa using Morisita similarity index with a threshold of 0.6 and compared niche overlap with null models within and between FFGs. Observed variance of niche overlap was greater than expected by chance, confi rming the presence of FFGs among analyzed taxa. Considering trophic similarity of species, we identified four FFGs: collectors, omnivores, herbivores and predators. Niche overlap was greater than expected by stochastic null models within FFGs, and smaller between FFGs. Nearly one third of analyzed taxa were classified in a diff erent FFG than their congeners of the Holarctic region. This result indicates that classifications performed in the Holarctic region should be used with care in the Neotropical region, even in subtropical systems.